(untitled) (Research, Society and Development, 2021)
Capsicum spp. is a spice used in different ways in food, fresh or industrialized, and in various gastronomic cultures. The rich bioactive profile and antioxidant properties attributed to peppers highlights the species Capsicum annuum var. annuum "jalapenho" for presenting sensory and nutritional characteristics that favor its consumption and industrial processing. The main aim of this work was to characterize the jalapeño pepper (Capsicum annuum L. var. annuum) in its centesimal composition, physicochemical, bioactive compounds and antioxidant capacity. The results showed that the fruit of the jalapeño pepper presented a nutritional value similar to peppers of its species and also of other species. The physical-chemical analyzes express desirable results for the processing of products derived from pepper, with moderate acidity (0.41 ± 0.01 g.100g-1) and hue between orange and red (hº = 55.17). The antioxidant activity was demonstrated by the methods of DPPH, FRAP and ABTS for the aqueous extracts of the jalapeño pepper fruit, with 360.00 ± 5.00 µM TE.g-1, 121.47 ± 2.54 µM FSE.g-1 and 107.40 ± 1.16 µM TE .g-1, respectively, obtaining higher activity by the FRAP and ABTS methods. The bioactive compounds showed levels of 474.64 ± 12.26 mg GAE.100g-1 of phenolic compounds, 112.88 ± 0.36 mg QE.100g-1 of total flavonoids, 3.79 ± 0.26 mg.100g-1 β-carotene and 2.72 ± 0.19 mg.100g-1 lycopene, demonstrating that the jalapeno pepper is an expressive source of these bioactive compounds and is a raw material of interest for the food industry.